TEACHING STUDENTS TO SOLVE TRIGONOMETRIC EQUATIONS USING ELEMENTS OF MATHEMATICAL ANALYSIS IN MATHEMATICS CIRCLES (American Journal of Technology and Applied Sciences, 2023)
Mathematics circles, mathematics is the main type of work outside the classroom. Circles arouse students' interest in science and improve their mathematical thinking, skills, and the quality of their mathematical training. This increases students' thinking range.